ANALISIS RESEPSI FOLLOWERS @KEMENKESRI TERHADAP AKUN TIKTOK KEMENKES RI SEBAGAI MEDIA INFOMASI COVID-19 - Maulia Pratiwi (2024)
Today's delusions use social media to find information and news. The presence of the Ministry of Health of the Republic of Indonesia on Tiktok social media provides various Covid-19 health education messages through Creative videos. This matter attracted the attention of the community until finally discussed by the public. The purpose of this study is to determine the meaning of @kemenkesri followers in perceiving @kemenkesri accounts as Covid-19 information media. This research uses the theory of encoding-decoding from Stuart Hall, this theory talks about the meaning of information by communicants can be different from that conveyed by communicators. The research method used is descriptive qualitative using primary data sources in the form of videos in Tiktok accounts @kemenkesri and interviews with informants as well as secondary data in the form of previous research, books and journals with similar topics. The data collection technique used in this study was an in-depth interview. The results obtained from the study show that the meaning of informants has a diversity of meanings based on their backgrounds. Audience classification based on the results of its meaning: (1) Dominant Hegemonic Position, M, DA, EPS, and RFS informants understand the message as it is. The message can be generally accepted so that the audience can interpret the signs, (2) Negotiated Position, AS, AA, and IN informants make selections to receive which signs match them, (3) Oppositional Position, there are no opposition informants in this study who really refuse to agree with the message conveyed by the Ministry of Health. The difference in meaning possessed by informants is based on several factors, namely mindset, education, experience, and knowledge